Neue Alabasterfragmente aus dem Sarkophagdeckel Sethos‘ I. im Kairener Museum - Ghany, Khaled Abdel (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
This article presents the publication of three royal calcite fragments from the basement of the Egyptian museum Cairo, illustrated with different funerary depictions on both sides. On the front side they are decorated with varied sections from the sixth, seventh and eighth hour of the Book of the Gate – showing also at one of them the personal name with a cartouche of Seti I, and on the reverse side there are some small texts from the spells 72, 180, 181 of the Book of the Dead inscribed. Due to their depicted scenes and textual representations, these fragments refer to the same decorative program of the fragments of the sarcophagus lid of Seti I, and also their characteristic traits show consistency with the similar iconographic and the paleographic features of the lid’s fragments. Thus, these fragments can be identified as part of the sarcophagus lid of Seti I and belonging to his decoration units, which are providing an innovative perspective for illustrated funerary literature and a significant combination between an underworld book and other diverse religious texts at the beginning of 19th Dynasty.